Do 'pathologic' cardiac murmurs in adolescents identify structural heart disease? An evaluation of 15 141 active adolescents for conditions that put them at risk of sudden cardiac death. Issue 2 (15th January 2021) - Austin, Ashley V; Owens, David S; Prutkin, Jordan M; Salerno, Jack C; Ko, Brian; Pelto, Hank F; Rao, Ashwin L; Siebert, David M; Carrol, Jennifer S; Harmon, Kimberly G; Drezner, Jonathan A
Abstract : Objectives: We assessed whether the presence and character of a cardiac murmur in adolescents were associated with structural heart disease that confers risk of sudden cardiac death (SCD). Methods: We performed a retrospective analysis of 15 141 adolescents age 12–19 who underwent a heart screen with history, physical examination and ECG. Participants with any screening abnormality underwent an echocardiogram for the assessment of structural heart disease. Murmurs were classified as physiological or pathological according to standard clinical criteria, and participants with murmurs were compared with a comparison group without murmurs. The primary outcome was echocardiogram-detected structural heart disease associated with SCD. Results: 905 participants with a cardiac murmur (mean age 15.8; 58% male) and 4333 participants without a murmur (comparison group; mean age 15.8; 55% male) had an echocardiogram to detect structural heart disease. 743 (82%) murmurs were described as physiological and 162 (18%) as pathological. Twenty-five (2.8%) participants with murmurs and 61 (1.4%) participants without murmurs had structural heart disease. Three (0.3%) participants in the murmur group were diagnosed with hypertrophic cardiomyopathy (HCM) which was the only identified condition associated with SCD. Two participants with HCM had physiological murmurs, one had a pathological murmur, and all three had an abnormal ECG. The most common minor structural heart disease was bicuspid aortic valve in both the murmur (7; 0.8%) and comparison (20; 0.5%) groups. The positive predictive value of physiological versus pathological murmurs for identifying any structural heart disease was 2.4% versus 4.3% (p=0.21), respectively. The positive predictive value of having any murmur versus no murmur for identifying structural heart disease was 2.8% versus 1.4% (p=0.003), respectively. Conclusions: In adolescents, the traditional classification of cardiac murmurs as 'physiologic' or 'pathologic' does not differentiate for structural heart disease that puts individuals at risk for SCD. We recommend ECG evaluation in all patients with a cardiac murmur found during preparticipation screening to increase detection of HCM.